Arthroscopic Long Thoracic Nerve Decompression for Painful Scapulothoracic Abnormal Motion: Technique and Indications - Ryan Lohre, M.D.; Abdulaziz F. Ahmed, M.D.; Bassem Elhassan, M.D. (Arthroscopy Techniques)
Patients with abnormal motion and winged scapula can present with debilitating pain and shoulder dysfunction. Multiple etiologies of scapulothoracic abnormal motion have been described, including muscle paralysis secondary to nerve injury or compression and discordant muscle activation secondary to pectoralis minor hyperactivity. In patients with intact serratus anterior musculature and clinical evidence of pain along the serratus anterior and long thoracic nerve (LTN) distribution, surgical release of the LTN is indicated. Previous publications have outlined both supraclavicular, thoracic, and combined open surgical approaches with varying results. This Technical Note provides an alternative, all-arthroscopic approach to thoracic decompression of the LTN.